IN VITRO EVALUATION OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS* (Indian Journal of Animal Production and Management, 2015)
Forty two different complete rations were formulated by using the sugarcane by products and other crop residues and evaluated through in vitro studies to select best combinations for preparation of complete rations for growth and milk production in buffaloes. Three graded Murrah buffalo bulls fitted with permanent rumen cannulae were used for in vitro evaluation of experimental rations. The average body weight of the buffalo bulls was 250 ± 1.0 kg. The fistulated buffalo bulls were maintained on a feeding regimen comprising of roughage and concentrate at 70:30 ratio. These animals were offered 2 kg of non leguminous green fodder (Hybrid Napier) and concentrate mixture daily at 8.00 am and 1.00 pm, while sugarcane bagasse was offered throughout the day these complete rations were evaluated for In vitro Dry Matter Digestibility (IVDMD) %. These complete rations containing 20 per cent sugarcane trash, sorghum straw, paddy straw, urea treated sugarcane trash, pillipesara hay or sunhemp hay along with 40 per cent each of sugarcane tops and concentrate component. The average IVDMD (%) of sugarcane by-product based complete ration was 54.14 ± 4.73 (Table 7.)
Keywords: Complete rations; In vitro; sugarcane by-products